ASSESSING THE IMPACT OF PERFROMANCE MEASUREMENT SYSTEMS IN NORTHERN NIGERIA SMALL BUSINESSES - Sunny Akpabot; Zulf Khan (European Scientific Journal, ESJ, 2015)
Small and Medium-Size Enterprise (SME) growth is on the rise in some of the world’s wealthier economies, resulting from their role play in job creation and revenue generation, through tax for local and central governments. Many SME practitioners around the world, mostly from the low and middle income countries, are mounting pressures on their governments to increase their involvement and support for the SME sector to help maintain its pace. This study aims to evaluate the impact of Performance Measurement System implementation in SMEs; it was carried out with the purpose of assessing whether PM Systems contribute positively or otherwise in SME growth. The outcomes of the study are intended to increase understanding of the impact PM Systems have on SMEs. This study employed questionnaires as a primary method for data collection.